Effect of protein hydrolysates from carp (Cyprinus carpio) skin gelatine on oxidative stress biomarkers and other blood parameters in healthy rats. (September 2019) - Tkaczewska, Joanna; Borczak, Barbara; Piątkowska, Ewa; Kapusta-Duch, Joanna; Morawska, Małgorzata; Czech, Tomasz
Graphical abstract: Highlights: Carp skin gelatine hydrolysate is safe for laboratory animals. Carp skin gelatine hydrolysate have very low biological value. Carp skin gelatine hydrolysate have promising antioxidant activity in vivo. Abstract: Carp skin gelatine hydrolysates can be a potential source of bioactive peptides with strong antioxidant properties tested in vitro, but there is no information on in vivo activity . Therefore, the objective of this study was to determine the ability of an antioxidant carp skin gelatine hydrolysate to attenuate plasma/serum levels of some oxidative stress markers in healthy adult Wistar rats. Analysis of hydrolysate included safety in an animal organism (haematological blood parameters, CRP, hepatic and kidney function), biological value (BV, TD, NPU), evaluation of the lipid profile (TC, LDL-C, HDL-C, TAG) and antioxidant blood status (TAS, MDA, GSR, HO-1). The results indicate that fish protein hydrolysates are safe for laboratory animals, but have very low biological value. An increase in glutathione reductase activity in the blood serum of healthy animals fed with carp skin gelatine hydrolysate supplements is a promising indicator of its antioxidant in vivo properties.